الانتخابات التشريعية في ظل الدستور الجزائري 2020 - مجناح سامي - بن مشيش فارس (جامعة المسيلة, 2022)
تجسد الانتخابات الوسيلة الديمقراطية الأمثل لمشاركة المواطنين في تسيير شؤونهم العامة وتعبيرهم عن قناعاتهم وخياراتهم بكامل حرية واستقلالية، ويظهر ذلك خصوصا من خلال عملية انتخابية نزيهة وشفافة بكامل مراحلها يتم فيها احترام الضوابط والنصوص القانونية المنظمة لإجرائها من كافة الأطراف. ولعل أهم ضمانات تحقيق تلك النزاهة هو ما تضمنه التعديل الدستوري لعام 2020 الذي نص على وجود إدارة مستقلة ممثلة في السلطة الوطنية المستقلة للانتخابات تشرف على جميع العمليات الانتخابية من بدايتها إلى غاية إعلان نتائجها، ويحكم عملها مبادئ مثل الحياد والاستقلالية لتصل إلى تحقيق عملية انتخابية نزيهة وشفافة، كما أن النظام الانتخابي الذي ينتهج أنماط وأساليب انتخابية سليمة ومدروسة هدفه الوحيد هو الحفاظ على صوت الناخب من كل تحريف أو تزوير هو النظام الانتخابي السليم، وهو الذي يضمن بجانب حق الانتخاب حقا آخر وهو الحق في الترشح، ويحدد شروطه و كيفياته بالطرق السليمة دون تعسف أو إقصاء، وهو ما حاول الأمر21-01 النص عليه و الأخذ به بغية الوصول إلى عملية انتخابية نزيهة وشفافة. الكلمات المفتاحية: العمليات الانتخابية – أمر 21-01 – شروط الترشح. Abstract: The elections are the best democratic way for the citizens to participate in the management of their daily life and business and therefore to express themselves and their choice and convictions with freedom and independence. All these could be done and realized by a clean and transparent election all along its steps by respecting the laws by everyone. Perhaps the most important of guarantees to achieve that integrity is what was included in the Constitutional Amendment of 2020, which stipulated the existence of an independent administration represented by the Independent National Elections Authority that supervises all electoral processes from its inception to the point of announcing its results, and its work is governed by principles such as neutrality and independence in order to achieve a fair and transparent electoral process, as well as The electoral system that adopts sound and studied electoral patterns and methods whose sole goal is to preserve the voter's vote from any distortion or fraud is a sound electoral system, which guarantees, in addition to the right to vote, another right, which is the right to run, and defines its conditions and modalities in the right ways without arbitrariness or exclusion. This is what Ordinance 21-01 tried to stipulate and adopt in order to reach a fair and transparent electoral process. Keywords: The electoral process - Order 21-01 - Conditions for candidacy.
Keywords: العمليات الانتخابية – أمر 21-01 – شروط الترشح